2005
DOI: 10.1021/ol047570e
|View full text |Cite
|
Sign up to set email alerts
|

LDA-Catalyzed Cycloisomerization of 2-(2-Propynyloxy)ethyl Iodides Leading to 3-(Iodomethylene)tetrahydrofurans

Abstract: LDA catalyzes cycloisomerization of 2-(2-propynyloxy)ethyl iodides to give 3-(iodomethylene)tetrahydrofurans. The reaction is proposed to proceed through a mechanism involving exo-cyclization of an alkynyllithium intermediate and protonation of the resulting alkylidene carbenoid by the starting iodide. [reaction: see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…15 The proposed reaction mechanism is a combination of Knorr's type process, proposed for the formal substitution of a vinyl bromide by an organolithium compound, 16 and the process proposed by the authors for a cyclization reaction of ωiodoalkynes. 17 The I/Li exchange reaction of iodoalkyne 56 with RLi affords the corresponding lithium acetylide 57, which undergoes an exo-trig cyclization followed by a vinylic substitution of the cycloalkylidenecarbenoid to produce the alkenyllithium intermediate 59. I/Li exchange furnishes the final product 60 (Scheme 15).…”
Section: Alkylidenecyclopropanes 21 Syntheses Of Methylene-and Alkyli...mentioning
confidence: 99%
“…15 The proposed reaction mechanism is a combination of Knorr's type process, proposed for the formal substitution of a vinyl bromide by an organolithium compound, 16 and the process proposed by the authors for a cyclization reaction of ωiodoalkynes. 17 The I/Li exchange reaction of iodoalkyne 56 with RLi affords the corresponding lithium acetylide 57, which undergoes an exo-trig cyclization followed by a vinylic substitution of the cycloalkylidenecarbenoid to produce the alkenyllithium intermediate 59. I/Li exchange furnishes the final product 60 (Scheme 15).…”
Section: Alkylidenecyclopropanes 21 Syntheses Of Methylene-and Alkyli...mentioning
confidence: 99%
“…The use of inexpensive, nontoxic alkali, alkali earth, and main group elements in the place of transition metals in catalysis is a rapidly developing field. Recently, it was found that tetramethylethylenediamine (TMEDA)-supported lithium amides are catalysts for the guanylation of electron-deficient amines, operating efficiently under mild reaction conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we wish to report cycloisomerization of iodoalkynes and diiodoalkynes to afford (iodomethylene)- and (diiodometh-ylene)cycloalkanes through a novel carbenoid-chain process involving exo -cyclization of the acetylide intermediate. The extension of the reactions to an atom-transfer-type cyclization of 13 (eq 4) as well as some mechanistic aspects in exo -cyclization of acetylides are also described …”
Section: Introductionmentioning
confidence: 99%